Sexualised masculinity men's bodies in 21st century media culture - Mercer, John 1966-; Smith, Clarissa (Routledge, 2025)
"Sexualised Masculinity: Men's Bodies in 21st Century Media Culture explores evolving portrayals of masculinity in contemporary media, focusing on the increasing eroticisation of the male body. This book examines how traditional and digital media-from films and television to social media platforms and fashion-have transformed the ways masculinity is represented and perceived. Through a wide array of case studies, it highlights how male bodies are now sites of erotic value, challenging long-standing norms and expectations. By exploring both global and local media, John Mercer and Clarissa Smith provide insights into the shifting landscape of gender and sexuality, offering a critical perspective on how masculinity is consumed, performed, and commodified in today's world. This book is essential for students and scholars in fields such as gender studies, media studies, cultural studies, and social history, and is particularly relevant for those interested in understanding the intersections of masculinity, media, and sexuality in the 21st century."
Keywords: Geschichte 2000-2025; Körper; Männlichkeit; Massenmedien; Mann; Masculinity in mass media; Sex in mass media; Human body in mass media; Masculinité dans les médias; Sexualité dans les médias; Corps humain dans les médias